Need Assessment of Women's Prison Class IIB Batam Business Incubator Assistance - Youlandita Kaka Safira Manurung; Lokita Rizky Megawati; Dikky Indrawan (School of Business, IPB University (SB-IPB), 2022)
Self-reliance development of independence at the Class IIB Batam Women's Penitentiary can be indicated to be less intensive because the flow of guidance is still unclear so the purpose of fostering independence has not been fully realized. Therefore, an appropriate mentoring model is needed to complete the objectives. One of the facilities that play a role in business assistance is a business incubator. This study aims to identify the need for Tanjak independence development and the establishment of an appropriate business incubator mentoring model for the Class IIB Batam Women's Prison. Qualitative analysis is needed to identify the need for Tanjak independence development and the establishment of a business incubator mentoring model. In addition, the analysis of VPEC-T and MoSCoW is also needed as input for the mentoring model. The results of this study were designed based on the priority needs and expectations of parties related to the development of Tanjak independence. Keywords: business incubator, mentoring model, MoSCoW, Tanjak, VPEC-T